Answer:
Choice 1 is true answer.
Explanation:
We have given two equations.
x+2y = 5 eq(1)
3x+5y = 14 eq(2).
we use substitution method to solve this system of equations.
From eq(1), separate x.
x = 5-2y eq(3)
substituting the value of x in eq(2)
3(5-2y)+5y = 14
15-6y+5y = 14
Adding -15 to both sides of above equation, we have
-15+15-6y+5y =-15+14
Adding like terms ,we have
-y = -1
y = 1
Substituting the value of y in eq(3),we have
x = 5-2(1)
x = 5-2
x = 3
hence, the solution of given system is (3,1).